1994
DOI: 10.1002/abio.370140107
|View full text |Cite
|
Sign up to set email alerts
|

Production of propionic acid by microbiological way. Part 2. Effect of the pH value on cell growth and acid production

Abstract: The batch propionic acid fermentation of sugar cane molasses by Propionibacterium acid propionici PP-I was studied at various pH values ranging from 5 to 7. The optimum pH range for cell growth was between 6 and 7, whereas the specific growth rate decreased with the pH in the acidic range down to 0.197 h-' at pH 5. The propionic acid yield increased with decreasing pH; it changed from 22% (wt/wt) at pH 7 to 38% at pH 5. It has been obvious that this process is inhibited by the products of the fermentation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, it was more suitable for the cell growth at pH 6.5 and 8.26 g/l of DCW was obtained. It was indicated that the optimum pH for cell growth was not suitable to the propionic acid production [14,15]. According to the above results, it was necessary to investigate the role of pH for cell growth and propionic acid production by P. freudenreichii CCTCC M207015.…”
Section: Time Course Of Propionic Acid Fermentation At Different Ph Vmentioning
confidence: 95%
“…However, it was more suitable for the cell growth at pH 6.5 and 8.26 g/l of DCW was obtained. It was indicated that the optimum pH for cell growth was not suitable to the propionic acid production [14,15]. According to the above results, it was necessary to investigate the role of pH for cell growth and propionic acid production by P. freudenreichii CCTCC M207015.…”
Section: Time Course Of Propionic Acid Fermentation At Different Ph Vmentioning
confidence: 95%